ANALYSIS OF FINANCIAL INSTITUTIONS CREDIT IMPACT ON MSE INCOME IN BALI PROVINCE - Putra, Ksama; Setyari, Ni Putu Wiwin (Jurnal Ekonomi Kuantitatif Terapan; 2021: Vol. 14, No. 2, Agustus 2021 (pp.243-431), 2021)
Micro and Small Enterprises (MSEs) are a business scale that dominates the national economy and the regional economy of Bali. Playing a strategic role, MSEs still have limitations in developing their businesses. One solution to overcoming this limitation is through additional capital through business credit lines from financial institutions. With additional capital, business actors can expand marketing, add production factors, improve output quality and so on. But on the other hand, the impact of credit also has a negative effect. Regular debt payments and additional payments through credit interest are the things that affect the smoothness of the company's financial balance. This study aims to determine the impact of credit on MSE income in Bali. The data used are SE2016-Advanced and PODES (BPS) data. The research method uses the analysis technique Propensity Score Matching (PSM). Based on processing results, credit has a significant positive impact on MSE income.